HIGHLY RESOLVED BERYLLIUM-10 RECORD FROM ODP SITE 1089-A GLOBAL SIGNAL? - Christl M.; Mangini A.; Kubik P.W. (My University, 2007)
In this study a highly resolved Beryllium-10-record from a rapidly accumulating sediment core located in the Southern Cape Basin (ODP Leg 177 Site 1089) is presented. To extract the global 10Be-production signal from the sedimentary record a dedicated correction procedure is applied. First, sediment redistribution is quantified by applying Thorium-230-normalization, then lateral transport of 10Be and 230Th is assessed using simple box model calculations. The model results indicate that only minor transport corrections have to be applied. Thus, Site 1089 combines the advantage of good time resolution with nearly negligible oceanic transport of 10Be leading to a favored site for the reconstruction of global 10Be-production changes from marine sediments. Our results suggest that the transport corrected 10Be-record at Site 1089 reflects long-term variations of the global 10Be-production rate over the past 300 kyr. The absolute values of the youngest (Holocene) samples are in good agreement with the estimated recent long-term averaged global 10Be-production rate (deduced from observations). The variability of the 10Be-flux over the past 300 kyr corresponds well to the expected range (deduced from model calculations). The comparison with other reconstructions of geomagnetic paleointensity and with records of cosmogenic nuclides further emphasizes the global character of this 10Be-record. Therefore, our results show that it is possible to quantitatively extract the global 10Be-production rate from a single marine record if transport processes are corrected for. Since the error of a single reconstruction is large a combination of several highly resolved and transport corrected 10Be-records may lead to a significantly improved reconstruction of geomagnetic variability and of global cosmic ray flux and over the past 300 kyr. © 2007 Elsevier B.V. All rights reserved.
Keywords: BERYLLIUM-10; COSMIC RAYS; COSMOGENIC RADIONUCLIDES; GEOMAGNETIC PALEOINTENSITY; SOUTHERN OCEAN; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен